From service quality to loyalty: The role of satisfaction in international students in South America - Inaguazo, Jazmin; Chavez, Dania; Machaca, Carlos; Paz, Jose; Marín, Carlos; Mendivelso, Harold (Journal of International Students, 2026)
In higher education, quality of service has been recognized as an essential element for achieving student satisfaction and loyalty. This study analyzed the influence of service quality on the satisfaction and loyalty of 140 international students from 26 countries, from three South American universities. The dimensions of the SERVQUAL showed high internal consistency (a= 0.816-0.892), while Satisfaction (a=0.95) and Loyalty (a=0.902) showed high reliability. The SEM with DWLS estimator showed satisfactory adjustment indices (CFI=0.996; TLI=0.995; RMSEA=0.077), as the quality of the service positively and significantly influenced Satisfaction (b=0.679; R2=0.461), which influenced Loyalty (b=0.889; R2=0.859); on the other hand, quality did not impact it (b=0.055), unlike the high indirect effect mediated by satisfaction (b=0.603); results that confirm how relevant satisfaction is in the formation of institutional loyalty in internationalized contexts.